Composition of human faecal microbiota in resistance to Campylobacter infection. (January 2016) - Kampmann, C.; Dicksved, J.; Engstrand, L.; Rautelin, H.
Abstract: In mice, specific species composition of gut microbiota enhances susceptibility to Campylobacter jejuni but little is known about the specific composition of the human gut microbiota in providing protection from infections caused by enteropathogens. Healthy adult individuals, who travelled in groups from Sweden to destinations with an estimated high risk for acquisition of Campylobacter infection, were enrolled. Faecal samples, collected before travelling and after returning home, were cultured for bacterial enteropathogens, and analysed for Campylobacter by PCR and for the species composition of the microbiota by 16S amplicon massive parallel sequencing. The microbiota compositions were compared between persons who became infected during their travel and those who did not. A total of 63 participants completed the study; 14 became infected with Campylobacter, two with Salmonella and 47 remained negative for the enteropathogens tested. After exclusion of samples taken after antimicrobial treatment, 49 individuals were included in the final analyses. Intra-individual stability of the microbiota was demonstrated for samples taken before travelling. The original diversity of the faecal microbiota was significantly lower among individuals who later became infected compared with those who remained uninfected. The relative abundances of bacteria belonging to the family Lachnospiraceae, and more specifically its two genera Dorea and Coprococcus, were significantly higher among those who remained uninfected. The travel-related infection did not significantly modify the faecal microbiota composition. Species composition of human gut microbiota is important for colonization resistance to Campylobacter infection. Especially individuals with a lower diversity are more susceptible to Campylobacter infection.